Mangroves and associated vegetation under metals and arsenic lingering impact: the legacies of zinc smelter industry residues and iron ore in southeast Brazil - Kütter, Vinicius Tavares; Costa, Ingrid Tavares; Pires, Alina Criane de Oliveira; Montes-Bayón, Maria; Sanz-Medel, Alfredo; Machado, Wilson; Silva Filho, Emmanoel Vieira (Frontiers in Ocean Sustainability, 2025)
IntroductionMangrove forests play a crucial role in the biogeochemical cycling of trace elements in intertropical coastal regions. This study evaluates concentrations of metals and arsenic in mangrove plants and ferns (leaves, flowers, branches, and roots) along a tidal creek chronically affected by residues from a zinc smelter and along another creek influenced by iron ore storage in Sepetiba Bay, Rio de Janeiro, Brazil.MethodsTo investigate potential physiological responses to metal exposure, selected plant samples were analyzed for the occurrence of proteins like phytochelatins. Total element contents (As, Zn, Cd, Cr, Cu, Mn, Fe, Ni, and Pb) were determined using ICP-MS, and the proteins were analyzed through SEC-HPLC-ICP-MS.ResultsElevated concentrations of As (average of 34.81 mg kg−1) were detected in fern leaves, and proteins similar to phytochelatins indicated the presence of two distinct chemical species of As in these plants. In mangrove trees, three chemical species were identified in leaves and two in flowers and branches. Statistical comparisons showed significant differences in Cr, Cu, and Pb in mangrove leaves and Pb in branches from the Arapucaia Channel relative to Saco do Engenho Creek. These higher concentrations were associated with untreated domestic effluent from the Mazomba River and effluent from ore and coal activities in Itaguaí Port.DiscussionResults indicate a dilution gradient for all metals (except Fe) from the former Cia Mercantil Ingá waste site toward the bay, whereas the Arapucaia Channel does not show a comparable dilution pattern. These outcomes highlight consideration contaminant sources, hydrodynamics, and plant uptake pathways in managing mangroves in higher polluted area.